Prostate Health Index Density Outperforms Prostate Health Index in Clinically Significant Prostate Cancer Detection - Chiu, Shih-Ting; Cheng, Yung-Ting; Pu, Yeong-Shiau; Lu, Yu-Chuan; Hong, Jian-Hua; Chung, Shiu-Dong; Chiang, Chih-Hung; Huang, Chao-Yuan (Frontiers in Oncology, 2021)
Background: Prostate-specific antigen (PSA) is considered neither sensitive nor specific for prostate cancer (PCa). We aimed to compare total PSA (tPSA), percentage of free PSA (%fPSA), the PSA density (PSAD), Prostate Health Index (PHI), and the PHI density (PHID) to see which one could best predict clinically significant prostate cancer (csPCa): a potentially lethal disease. Methods: A total of 412 men with PSA of 2–20 ng/mL were prospectively included. Serum biomarkers for PCa was collected before transrectal ultrasound guided prostate biopsy. PHI was calculated by the formula: (p2PSA/fPSA) x √tPSA. PHID was calculated as PHI divided by prostate volume measured by transrectal ultrasound. Results: Of the 412 men, 134 (32.5%) and 94 (22.8%) were diagnosed with PCa and csPCa, respectively. Areas under the ROC curve for tPSA, %fPSA, %p2PSA, PSAD, PHI and PHID were 0.56、0.63、0.76、0.74、0.77 and 0.82 respectively for csPCa detection. In the univariate analysis, the prostate volume, tPSA, %fPSA, %p2PSA, PHI, PSAD, and PHID were all significantly associated with csPCa, and PSAD and PHID were the most important predictors (OR 1.24, 95% CI 1.07–1.44, and OR 1.41, 95% CI 1.15–1.72, respectively). At 90% sensitivity, PHID had the highest specificity (54.1%) for csPCa and could reduce the most unnecessary biopsies (43.7%) and miss the fewest csPCa (8.5%) when PHID ≥ 0.67. The PHID cut-off value was positively correlated with the csPCa ratio in the PHID risk table, which is useful for evaluating csPCa risk in a clinical setting. Conclusion: The PHID is an excellent predictor of csPCa. The PHID risk table may be used in standard clinical practice to pre-select men at the highest risk of harboring csPCa.